Türkiye'de kadın hareketinin kurumsallaşması - Karahan, Sebahat Duran (My University, 2018)
Bu çalışmanın temel amacı, Türkiye’de kadın hareketinin oluşum dinamiklerini söylem ve eylem üzerinden incelemek ve bu örgütsel alanda gerçekleşen değişimi yeni kurumsal kuram perspektifinden irdelemektir. Araştırmada 1980-2010 yılları arası gazete ve dergi tarama yöntemi ile kadın hareketinin kurumsallaşma basamakları, söylem analizi ve yıllar içerisinde meydana gelen örgütsel değişimi incelenmektedir.Çalışmanın bulguları kadın hareketinin sembol ve unsurlarının farklı yıllarda kurumsallaştığını, örgütsel değişimin ise dışsal etkiler ile gerçekleştiğini göstermektedir.

The fundamental aim of this research is to examine the formation dynamics of the women’s movement through discourse and action, as well as to analyze the shift that has occurred within this organizational area in Turkey through the lens of neoinstitutionalism. This research had examined the institutionalization steps of women’smovement and the organizational change occurred throughout between the years 1980 and 2010 through the scanning and discourse analysis of newspapers and magazines. The findings of the study suggest that the symbol of the women’s movement and its elements had been institutionalized at different points in time, and that organizational change had been caused by the external forces.
Keywords: Feminism; Feminizm; feminizm New institutional theory; institutionalchange; institutionalization; kadın hareketi; Kadınlar; kurumsaldeğişim; kurumsallaşma; Social conditions; Sosyal durum; Turkey; Türkiye; Women; women movement; Yeni kurumsal kuram